Water Quality Parameters and Bird Diversity in Jagdishpur Reservoir, Nepal - Thapa, Jham Bahadur; Saund, Tej Bahadur (Nepal Journal of Science and Technology, 2013)
Water quality parameters were analyzed seasonally to examine relationships with bird numbers and species richness in Jagdishpur reservoir. This wetland is a Ramsar site and an important bird area (IBA) of Nepal. The trophic status of the reservoir was categorized as eutrophic as assessed by Secchi disk transparency (1.45 ± 0.53 m), total alkalinity (220.94 ± 85.52 mg/l) and total nitrogen (884.19 ± 291.61 ?g/l) concentrations. Direct count method detected a total of 77 bird species belonging to 8 orders and 31 families of which 40 species were resident and 37 migrants. Species richness ranged from 21(summer) to 74 species (winter). Secchi disk transparency showed a significant positive correlation with bird numbers ((r = 1.00, p < 0.01) whereas significant negative correlation was found between water temperature and species richness (r = - 0.97, p < 0.05). Absolute positive correlation between species richness and seasons was established (r = 0.74). The seasonal distribution pattern showed two peaks of species richness, Shannon diversity, equitability and evenness index, one in winter and the other in autumn. Fulica atra (30.53%), Dendrocygna javanica (15.88%) and Anas strepera (9.58%) were the three most dominant bird species. Fourteen CITES species, 8 globally and 14 nationally threatened species were recorded. Conservation action plan for threatened species that focuses on population monitoring, protecting key habitats and habitat enhancement is urgently needed. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 143-155 DOI: http://dx.doi.org/10.3126/njst.v13i1.7453